Advancing sustainable chemistry education: Insights from real-world case studies - Evelyn Araripe; Vânia G. Zuin Zeidler (Current Research in Green and Sustainable Chemistry)
This study aims at analysing the integration of innovative teaching methodologies through the implementation of two case studies, “Plasticized Childhood” and “Unpacking Burgers,” in the context of Green Chemistry (GC) and Sustainable Chemistry (SC) education. The case studies were devised with the objective of engaging students in real-world scenarios, thereby fostering critical thinking and practical problem-solving skills. “Plasticized Childhood” examines the environmental and health impacts of plastic toys, while “Unpacking Burgers” delves into the complexities of plant-based meat alternatives. The Classroom Observation method was employed to systematically observe and analyse student interactions and learning outcomes. Our findings illustrate the transition from GC to SC, emphasising considerations beyond material substitution, such as marketing strategies and health implications. The case studies highlighted the pivotal role of the chemical industry in propelling sustainable innovation and the value of interdisciplinary approaches. One challenge was addressing student sensitivities around controversial topics, as well as the need for more specialised content in graduate programmes. The study illustrates the value of integrating real-world scenarios into chemistry education, equipping students with the skills and conditions to address sustainability challenges through innovative, ethical and responsible solutions. It would be beneficial for future research to concentrate on the improvement of case study methodologies and the strengthening of interdisciplinary collaborations, with the aim of further advancing sustainable chemistry education.